Reactive Oxygen Species Formation in the Brain at Different Oxygen Levels: The Role of Hypoxia Inducible Factors - Chen, Ruoli; Lai, U Hin; Zhu, Lingling; Singh, Ayesha; Ahmed, Muhammad; Forsyth, Nicholas R. (Frontiers in Cell and Developmental Biology, 2018)
Hypoxia inducible factor (HIF) is the master oxygen sensor within cells and is central to the regulation of cell responses to varying oxygen levels. HIF activation during hypoxia ensures optimum ATP production and cell integrity, and is associated both directly and indirectly with reactive oxygen species (ROS) formation. HIF activation can either reduce ROS formation by suppressing the function of mitochondrial tricarboxylic acid cycle (TCA cycle), or increase ROS formation via NADPH oxidase (NOX), a target gene of HIF pathway. ROS is an unavoidable consequence of aerobic metabolism. In normal conditions (i.e. physioxia), ROS is produced at minimal levels and acts as a signaling molecule subject to the dedicated balance between ROS production and scavenging. Changes in oxygen concentrations affect ROS formation. When ROS levels exceed defense mechanisms, ROS causes oxidative stress. Increased ROS levels can also be a contributing factor to HIF stabilization during hypoxia and reoxygenation. In this review, we systemically review HIF activation and ROS formation in the brain during hypoxia and hypoxia / reoxygenation. We will then explore the literature describing how changes in HIF levels might provide pharmacological targets for effective ischaemic stroke treatment. HIF accumulation in the brain via HIF prolyl hydroxylase (PHD) inhibition is proposed as an effective therapy for ischaemia stroke due to its antioxidation and anti-inflammatory properties in addition to HIF pro-survival signaling. PHD is a key regulator of HIF levels in cells. Pharmacological inhibition of PHD increases HIF levels in normoxia (i.e. at 20.9% O2 level). Preconditioning with HIF PHD inhibitors show a neuroprotective effect in both in vitro and in vivo ischaemia stroke models, but post stroke treatment with PHD inhibitors remains debatable. HIF PHD inhibition during reperfusion can reduce ROS formation and activate a number of cellular survival pathways. Given agents targeting individual molecules in the ischaemic cascade (e.g. antioxidants) fail to be translated in the clinic setting, thus far, HIF pathway targeting and thereby impacting entire physiological networks is a promising drug target for reducing the adverse effects of ischaemic stroke.